Відображення плинності часу в хореографічному мистецтві - Кравчук Олена; Kravchuk Olena; Федьо Каріна; Fedo Karina (Видавництво «Код», 2025)
Резюме. Стаття присвячена проблемі відображення плинності часу у хореографічному мистецтві як важливого аспекту художнього і психологічного сприйняття танцю.

Abstract. The article explores the problem of reflecting the fluidity of time in choreographic art as an important aspect of the artistic and psychological perception of dance. The purpose of the article is to consider the relationship between tempo, rhythm, composition of movements and spatial organization in creating the effect of continuity and cyclicity of time. Considerable attention is paid to the psychological aspect of the perception of time by dancers and spectators, as well as the role of improvisation and experimental choreographic techniques in the formation of subjective time. Historical and contemporary Ukrainian and foreign dance practices are analyzed, including folk choreography and modern forms of modern dance, with an emphasis on how changing the tempo, using pauses, repetitions and movement trajectories affect the sense of time in the performance. Separately, the methods of interaction of music, light and space to enhance the artistic sense of the fluidity of time are discussed. Choreographic art is perceived as a form of «living time», where each movement, pause or repetition acquires semantic meaning, and the compositional decisions of the artist-creator form in the viewer a sense of continuity and variability of time. The results of the study can be used in the practical activities of choreographers, choreography teachers, psychologists, as well as in scientific works devoted to cultural studies and art history.
Representation of the fluidity of time in choreographic art
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: хореографія; плинність часу; ритм; темп; рух; психологічне сприйняття